The Effect of Electronic Marketing (E-Marketing), Electronic Word of Mouth (E-Wom), Electronic Trust (E-Trust) on Electronic Satisfaction (E-Satisfaction) at Shopee Express in Ambon City - Asyura, Annisa Salsabillah Nur; Sitanipessy, Reiner .H; Tehuayo, Erlinda (ProBisnis : Jurnal Manajemen, 2024)
his study aims to determine the effect of Electronic Marketing (E- Marketing), Electronic Word of Mouth (E-Wom), and Electronic Trust (E- Trust) on Electronic Satisfaction (E-Satisfaction) at Shopee Express in Ambon City. This type of research is quantitative research. The population in this study were customers who had used Shopee Express services and the sample size was 154 respondents. By using a questionnaire as a sample collection tool. The sampling method used is non probability sampling with purposive sampling technique. The data analysis method used is Partial Least Square (PLS) and the data is processed using the help of SmartPLS software version 3.2.9. The results showed that E-Marketing has a positive effect on E- Satisfaction, E-Wom has a positive effect on E-Satisaction, E-Trust has a positive effect on E-Satisfaction.